Use of management techniques and hormones to control the time, rate, and regularity of lambing. - Nelson, E.A.; Smith, W.H.; Menzies, C.S. (Kansas Agricultural Experiment Station, 2011)
The experimental sheep used in conjunction with studies of summer fertility of sheep at the Kansas Agricultural Experiment Station consist of a commercial flock of approximately 136 head of western ewes of three predominant types (Texas or finewools, northwest blackface crossbreds, and northwest whiteface crossbreds) and four breeds of rams (Hampshire, Suffolk, Shropshire, and Southdown). Observations on the ewe flock during the past five years indicate that most ewes are sexually active during the summer months and that low summer fertility may be associated with the quality of the semen produced by the rams during the breeding season.
Keywords: Sheep; Management; Hormones; Lambing